Using protection motivation theory in the design of nudges to improve online security behavior. Issue 123 (March 2019) - van Bavel, René; Rodríguez-Priego, Nuria; Vila, José; Briggs, Pam
Highlights: We sought to influence (or nudge) security behaviour in an experiment in 5 EU countries, n = 2024. Coping messages were more effective than threat appeals in promoting secure online behaviour. Risk attitudes, age and country had a significant effect on security behaviour. Abstract: We conducted an online experiment ( n = 2024) on a representative sample of internet users in Germany, Sweden, Poland, Spain and the UK to explore the effect of notifications on security behaviour. Inspired by protection motivation theory (PMT), a coping message advised participants on how to minimize their exposure to risk and a threat appeal highlighted the potential negative consequences of not doing so. Both increased secure behavior – but the coping message significantly more so. The coping message was also as effective as both messages combined, but not so the threat appeal. Risk attitudes, age and country had a significant effect on behavior. Initiatives seeking to promote secure behavior should focus more on coping messages, either alone or in combination with fear appeals.